Distributional and efficiency impacts of clean and renewable energy standards for electricity - Rausch, Sebastian; Mowers, Matthew (Resource and energy economics, 2014)
We examine the efficiency and distributional impacts of greenhouse gas policies directed toward the electricity sector in a model that links a “top-down” general equilibrium representation of the U.S. economy with a “bottom-up” electricity-sector dispatch and capacity expansion model. Our modeling framework features a high spatial and temporal resolution of electricity supply and demand, including renewable energy resources and generating technologies, while representing CO2 abatement options in non-electric sectors as well as economy-wide interactions. We find that clean and renewable energy standards entail substantial efficiency costs compared to a carbon pricing policy such as a cap-and-trade program or a carbon tax, and that these policies are regressive across the income distribution. The geographical distribution of cost is characterized by high burdens for regions that depend on non-qualifying generation fuels, primarily coal. Regions with abundant hydro power and wind resources, and a relatively clean generation mix in the absence of policy, are among the least impacted. An important shortcoming of energy standards vis-à-vis a carbon pricing policy is that no revenue is generated that can be used to alter unintended distributional consequences.